A meta-analysis approach for determinants of effective factors on audit quality: Evidence from emerging market. Issue 2 (7th May 2019) - Salehi, Mahdi; Fakhri Mahmoudi, Mohamad Reza; Daemi Gah, Ali
Abstract : Purpose: The purpose of this paper is to demonstrate a deeper understanding about the reasons behind difference in previous studies' results in the field of audit quality determinants. Design/methodology/approach: A meta-analysis method is employed in which 52 studies including 40 international studies from authentic scientific articles during the year 2000–2015 and 12 national studies out of authentic national scientific articles from 2001 to 2015 are taken to account as sample studies. Audit firm size, auditor tenure and auditor specialization are set as independent variables and audit quality is the only dependent variable in the current paper. Findings: The results indicate that audit firm size and auditor specialization are positively associated with audit quality. In other words, contracting with larger audit firm and specialized auditor results in delivering higher quality audit services. Originality/value: The current study is the first study to be conducted in the field of audit quality determinants. The results may be beneficial both for standard setters as well practitioners in a way that it provides evidence that contributes to basis policy and audit-standard makers about domination and determinants of audit quality.